Computerized Stabilometry on a Four-Legged Platform for Comparative Analysis of Foot Positioning - Tarakanov, A. V.; Tarakanov, A. A.; Chebotov, S. A.; Efremov, V. V. (Biomedical engineering, 2021)
Computerized stabilometry using a four-legged stabilometric platform allows “free” positioning of the feet to be used, which is of fundamental importance for patients and subjects of different ages. The design of the stabilometric platform is important for finding the optimal positioning of the feet in controlling upright standing, treatment, and interpretation of results and comparison with other studies.